2000
DOI: 10.1053/eujp.2000.0167
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in regional brain response to visceral pressure in IBS patients

Abstract: In two experiments including a total of 30 irritable bowel syndrome patients, symptom-mimicking rectal pressure stimuli elicited changes in regional neural activation as measured by positron electron tomography (PET) cerebral blood flow images. Although most stimuli were not rated as painful, rectal pressure increased regional cerebral blood flow (rCBF) in areas commonly associated with somatic pain, including the anterior cingulate, insula, prefrontal cortex, thalamus, and cerebellum. Despite similar stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 50 publications
10
102
2
2
Order By: Relevance
“…In the present study, we did not observe any activations and/or deactivations in ACC, hippocampus, and amygdala, which could be due to the sex differences in brain activation patterns in response to rectal distension as supported by the previous studies reporting on the gender differences in visceral pain perception. [61][62][63][64] Furthermore, some studies reported activations in ACC during non-painful visceral distension implicating the role of this region in the control of autonomic visceral responses rather than to pain perception. 18,27,65,66 However, we observed the activations only during painful visceral distension, which might be another reason for the absence of activations in ACC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we did not observe any activations and/or deactivations in ACC, hippocampus, and amygdala, which could be due to the sex differences in brain activation patterns in response to rectal distension as supported by the previous studies reporting on the gender differences in visceral pain perception. [61][62][63][64] Furthermore, some studies reported activations in ACC during non-painful visceral distension implicating the role of this region in the control of autonomic visceral responses rather than to pain perception. 18,27,65,66 However, we observed the activations only during painful visceral distension, which might be another reason for the absence of activations in ACC.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing male and female IBS patients, greater mid-pINS and aINS activation was found during INF in male patients in two different samples (Berman et al, 2000;Naliboff et al, 2003) and greater activation of mOFC, dACC and amygdala in female patients in one study (Naliboff et al, 2003). The greater aINS activation in men was replicated in a third sample of healthy men and women using fMRI .…”
Section: Possible Correlation Of Findings With Previously Reported Spmentioning
confidence: 99%
“…Using SPM analysis of [ 15 O] water PET data, we have previously reported sex-related differences in the brain's response to an aversive visceral stimulus, despite overall similarity of activated regions (Berman et al, 2000;Berman et al, 2006;Naliboff et al, 2003). When comparing male and female IBS patients, greater mid-pINS and aINS activation was found during INF in male patients in two different samples (Berman et al, 2000;Naliboff et al, 2003) and greater activation of mOFC, dACC and amygdala in female patients in one study (Naliboff et al, 2003).…”
Section: Possible Correlation Of Findings With Previously Reported Spmentioning
confidence: 99%
See 1 more Smart Citation
“…8 While peripheral mediators likely affect GI motility, gender-associated differences in visceral pain perception in IBS patients have been demonstrated using brain imaging techniques such as positron emission tomography. 84 A study by Naliboff et al 85 has shown that compared to men with IBS, women with IBS utilized different areas of their brain, such as the amygdala, while experiencing a rectal distension they perceived as aversive. Moreover, other clinical studies have provided evidence that women's perception of visceral pain can be influenced by their cyclical changes in gonadal hormones.…”
Section: Sex Linked Differences In Visceral Sensitivitymentioning
confidence: 99%